(untitled) (Journal of Experimental and Clinical Anatomy, 2005)
This study was carried out to provide a data on the width, length and width to length ratio of Nigerian mandibles, which could be useful for anthropological and clinical purposes. It was a cross sectional anatomical study. Thirty dry adult Nigerian mandibles selected from bone collection of Anatomy Departments of some Nigerian universities were used. The length and width of the mandible were measured across the mental foramen using digital venier caliper and the width to length ration caliper and the width to length ratio calculated. The following were observed: the mean length for the right and left sides of the mandibles studied were 9.74 cm and 9.99cm respectively. The mean width for the right and left sides were 3.02cm and 2.97cm respectively while the width to length ratio for the right and left sides were 0.310 and 0.297 respectively. The difference observed between the right and left sides was not statistically significant (P>0.001). The width on the right and Ieft sides of Nigerian mandibles were approximately 13% respectively of the length of the mandible. These values are similar to some African populations but differ from other groups, most especially the Caucasians. The results of this study are reliable in anthropological study and clinical practice (Dentistry).